1982
DOI: 10.1271/bbb1961.46.717
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective synthesis of some isomers of dodecadien-1-ol: Compounds related to the pine moth sex pheromone.

Abstract: Four isomers of 5,7-dodecadien-l-ol were previously proposed as being the sex pheromone of the pine moth. The isomers were stereoselectively synthesized from 1-hexyne and tetrahydropyranyl ether of 5-hexyn-l-ol.The (5Z, 7Z)-isomer was synthesized by a Chodkiewic Cadiot reaction followed by hydroboration, and other three isomers by novel synthetic methods including the addition of zirconocene hydride [Schwarz's reagent (C5H5)2Zn(H)Cl] to control the regioselective coupling reaction. The 5,8-and 5,9-dodecadien-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1987
1987
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…This route seemed attractive due to the availability of starting (E)-7-dodecen-5-yn-1-ol through the palladium-catalyzed alkylation of tetrahydro-2-(5hexynyloxy)-2H-pyran with (E)-1-iodo-1-hexene (6). Ando et al (6) reported that Lindlar reduction of (E)-7-dodecen-5-yn-1-ol lacked selectivity, providing a mixture of (Z,E)-diene and monoenic compounds from which the desired product was isolated by chromatography on silica impregnated with silver nitrate. Stille and Simpson (7) used hydroboration of the protected (E)-7-dodecen-5-yn-1-ol to achieve high yield and purity of the pheromone.…”
Section: Introductionmentioning
confidence: 99%
“…This route seemed attractive due to the availability of starting (E)-7-dodecen-5-yn-1-ol through the palladium-catalyzed alkylation of tetrahydro-2-(5hexynyloxy)-2H-pyran with (E)-1-iodo-1-hexene (6). Ando et al (6) reported that Lindlar reduction of (E)-7-dodecen-5-yn-1-ol lacked selectivity, providing a mixture of (Z,E)-diene and monoenic compounds from which the desired product was isolated by chromatography on silica impregnated with silver nitrate. Stille and Simpson (7) used hydroboration of the protected (E)-7-dodecen-5-yn-1-ol to achieve high yield and purity of the pheromone.…”
Section: Introductionmentioning
confidence: 99%